PENGARUH CKS SEBAGAI PENGGANTI AGREGAT PADA KUAT TEKAN BETON - Zaki, Ahmad; Pratama, Titis Yoga; Wibisono, Candra Agung; Saleh, Fadillawaty (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
Concrete with oil palm shells (OPS) is an innovative alternative to normal concrete, which is increasingly expensive. In addition, reducing palm-based waste is the objective, one of which is waste that is no longer used in the form of palm shells. Therefore, OPS concrete can also be called green or environmentally friendly concrete. Thus, OPS concrete research becomes very important so that the effect of percentage (%) OPS on the compressive strength of concrete can be analyzed. A specimen in the form of a cylinder was used in this study. Such cylinders have dimensions with a diameter of 75 mm and a height of 150 mm. And the specimen consists of 5 variations of the specimen in the form of the percentage of OPS used, namely 0%, 10%, 20%, 30%, and 40% of the weight of the coarse aggregate (stone or gravel). Each specimen will be tested for compressive strength at concrete lifespans of 7, 14, and 28 days. In this study, the variation of oil palm shells with a percentage of 10% was the optimum value of compressive strength obtained. Compressive strength will decrease in concrete with a percentage above 10%. This happens because the increasing composition of OPS causes the concrete mixture's low workability so that the concrete's compressive strength value becomes lower.